Evaluating the correlation of Age and Gender with the Hematological Parameters of the Chronic Myeloid Leukemia Patients - Farooq I. Mohammad; Alaa R. Nadim (مجلة مركز بحوث التقنيات الاحيائية)
Background: White blood cell malignancy is known as chronic myelogenous leukemia (CML), or chronic myeloid leukemia. This type of leukemia is defined by the buildup of myeloid cells in the blood and their uncontrollably elevated proliferation in the bone marrow. A proliferation of adult granulocytes (neutrophils, eosinophils, and basophils) and their progenitors is observed in CML, a clonal bone marrow stem cell illness; a distinctive increase in basophils is clinically significant. This particular form of myeloproliferative neoplasm is linked to the Philadelphia chromosome, a distinctive chromosomal rearrangement. Methods: This was a cross-sectional hospital-based study carried out in Kirkuk Governorate, Iraq, from the beginning of  November  2022 to May 2023 on chronic myeloid leukemia patients in the Oncology and Hematology Center.  A total of 53 patients and 15 controls who were admitted and diagnosed with chronic myeloid leukemia based on complete blood count were included in the study. Incomplete data and patients who did not provide informed consent were omitted from the analysis. Results: A total of 53 patients were included in the study, with a mean age of 47.3±12.8 years. Mean HGB was 13.11±12.79 g/dl while HCT was 38.27±37.88%. PLT was 257.33±218.08 x109cells/mm3, WBC 4.77±4.61 x109 cells/mm3 , RBC 4.77± 4.61 x1012/L.  All statistics were implemented using statistical programs. Conclusion: The present study predicted the median age of 47.3 years in patients from chronic myeloid leukemia; a considerable difference did not exist in various Hematological parameters of male and female CML patients. It was concluded that no important difference in correlation was observed with age. A significant difference was observed in the platelet count of these patients on the basis of gender.